Health, information, perception and demographic variables as correlate of gender equality in science technology engineering and math (Stem) education in South-West Nigeria (2017)
Background: With the level of efforts and interventions by researchers and organizations around the world towards gender equality in Science Technology Engineering and Math (STEM), the number of women participation is still very low. UNESCO Institute for Statistics (2015) revealed that female representation is only about 30% of the total population in STEM while in Africa it is about 17% ( Ekine, 2013). This statistics, raises the question of what could be responsible for the resistant disparity? Could it be that girls at the foundational level do not have adequate career information about STEM and all it entails? What are their perceptions of Mathematics and sciences, are there some demographic issues? There is need to discover what the real causes of gender disparity in mathematics and sciences are from the junior secondary school, a period that precedes the choice subjects that form student’s career paths. This will provide an empirical basis for effectively bridging the gender gap in STEM in Nigeria thereby building and releasing the necessary latent human resources to sustain development and compete in the global economy as well as ensuring inclusivity of girls and women. Ekine (2013) affirmed that a country’s ability to secure good health, fight diseases, protect the environment, produce food for its people, and develop new industries and technologies is dependent on the scientific knowledge and skills of its people. Consequently, more women are needed in STEM to be active participants in scientific development particularly in health related issues, application and decision-making thus, ensuring that scientific initiatives are implemented to adequately address the needs and preferences of both sexes especially those of women. It is against this background that the study seeks to investigate Health, Information, Perception and Demographic variables as correlate of gender equality in STEM education in South-West Nigeria. On the long run, findings from a study such as this would highlight specific deficiencies associated with attracting and retaining girls in Mathematics and Science and proffer solutions to the problems.